Noradrenaline and acetylcholine responses of supraoptic neurosecretory cells - Barker, J. L. (1971)
1. Neurones in the supraoptic nucleus were examined for their responsiveness to microiontophoretically applied monoamines and cholinomimetic agents. One hundred and sixty-one of the 749 neurones recorded were antidromically identified as neurosecretory cells. 2. The monoamines, dopamine, noradrenaline and serotonin, reduced the activity of all cells which responded. 3. Reduction in activity following noradrenaline administration was antagonized by the β-adrenergic blocking agent MJ-1999 and potentiated by desmethylimipramine. 4. Acetylcholine produced either a decrease or an increase in activity of responsive cells with depression the predominant result. Both the depressant and the excitatory response to acetylcholine were seen in individual neurosecretory cells which were depressed by noradrenaline. 5. Application of acetyl-β-methylcholine and carbaminoylcholine consistently resulted in depression of all responsive cells, while nicotine excited the majority of responsive cells. Both types of response were observed on the same neurosecretory cell. 6. The depressant response was antagonized by the muscarinic blocking agent atropine while the excitatory response was antagonized by the nicotinic blocking agent dihydro-β-erythroidine. Responses to acetylcholine were potentiated by the acetylcholinesterase inhibitor physostigmine. 7. The data indicate that noradrenaline-containing terminals on these neurosecretory cells are likely to inhibit their discharge rate, while the presumed cholinergic terminals might function as either excitatory or inhibitory, depending on the receptor activated. 8. These results support the hypothesis that ADH release is related to the neuronal activity of the supraoptic neurosecretory cell.